Co9S8@carbon nanofiber as the high-performance anode for potassium-ion storage. Issue 25 (26th April 2021) - Xin, Wen; Wei, Zhixuan; Yao, Shiyu; Chen, Nan; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract : Co9 S8 @carbon nanofibers with boosted highly active electrode–electrolyte area, fast kinetics and controlled volume expansion show an excellent cycling and rate performance in potassium ion batteries. Abstract : Thanks to their intrinsic merits of low cost and natural abundance, potassium-ion batteries have drawn intense interest and are regarded as a possible replacement for lithium-ion batteries. The larger radius of potassium, however, provides slow mobility, which normally leads to sluggish diffusion of host materials and eventual expansion of volume, typically resulting in electrode failure. To address these issues, we design and synthesize an effective micro-structure with Co9 S8 nanoparticles segregated in carbon fiber utilizing a concise electrospinning process. The anode delivers a high K + storage capacity of 721 mA h g −1 at 0.1 A g −1 and a remarkable rate performance of 360 mA h g −1 at a high current density of 3 A g −1 . A small charge-transfer resistance and a high pseudocapacitive contribution that benefit fast potassium ion migration are indicated by quantitative analysis. The outstanding electrochemical performance can be attributed to the distinct architecture design facilitating high active electrode–electrolyte area and fast kinetics as well as controlled volume expansion.